2023
DOI: 10.3389/fresc.2023.1275808
|View full text |Cite
|
Sign up to set email alerts
|

Children then, adults now: long-term outcomes—performance at 15, 20, and 25 years of cochlear implant use

João Elói Moura,
Jorge Humberto Martins,
Marisa Alves
et al.

Abstract: MotivationSevere to profound sensorineural hearing loss interferes with a child's development at the cognitive, linguistic, academic, and social levels. Since the beginning of the pediatric auditory rehabilitation program through cochlear implantation in the Ear, Nose, and Throat (ENT) Service of the Coimbra Hospital and University Center (CHUC), Portugal, its mentors defended the early diagnosis of hearing loss followed by timely intervention, and this was considered the starting point to optimize (re)habilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Cochlear implants received in childhood and adulthood may show differences in performance as expected. Findings from various studies have shown that early implantation has more positive effects on auditory performance [ 19 , 20 ]. In our study, those receiving their implants in childhood reported more positive work performance compared to their counterparts implanted in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Cochlear implants received in childhood and adulthood may show differences in performance as expected. Findings from various studies have shown that early implantation has more positive effects on auditory performance [ 19 , 20 ]. In our study, those receiving their implants in childhood reported more positive work performance compared to their counterparts implanted in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for inclusion in the CI group were individuals with prelingual deafness who underwent cochlear implantation before the age of 3 years [ 13 ] and who were aged between 6 and 16 years [ 14 ] at the time of the evaluation. All participants were required to be unilaterally or bilaterally implanted with a MED-EL CI (MED-EL GmbH, Innsbruck, Austria), with at least 10 active electrodes, at least one year of stable fitting, and with good speech performance (defined as ≥65% of correctly identified disyllables in silence).…”
Section: Methodsmentioning
confidence: 99%